Improving the photoluminescence properties оf CdSe, CdSe/CdS semiconductor quantum dots for making solid-state laser active media - Stepanova, U. A.; Al-Mayyahi, H.; Khakimov, K. T.; Muradova, A. G.; Zaitsev, V. B.; Telminov, Evgenii N. (Nanobiotechnology reports)
The properties of CdSe, CdSe/CdS quantum dots in different reaction media are investigated. The effect of the reaction medium, duration and synthesis temperature exerted on the photoluminescence properties of the quantum dots is studied. Optimal synthesis conditions are chosen which make it possible to obtain quantum dots with no shell, having a high photoluminescence intensity in the range from 600 to 700 nm and characterized by the almost complete absence of luminescence defects. The CdS shell on CdSe quantum dots makes it possible to obtain an increase in the quantum yield ranging from 3.5 to 20%, as well as a decrease in the luminescence full width at half maximum (FWHM) as compared to nanocrystals with no shell. Nanocomposites based on PMMA and the synthesized quantum dots are developed for further use as laser active media.